Comparison of Anthropometric Indices in Predicting Metabolic Syndrome Components in Children - (:unkn) unknown (MARY ANN LIEBERT, INC, 2011)
Background: The International Diabetes Federation (IDF) defines metabolic syndrome among children. In addition to the abdominal obesity (waist circumference 90 percentile of locally representative sample), the risk criteria for metabolic syndrome includes elevated blood pressure, hypertriglyceridemia, low high-density lipoprotein cholesterol (HDL-C) levels, and elevated fasting glucose. In this study, we compared the association of anthropometric indices with metabolic syndrome risk criteria in 9-year-old children. Methods: A cross-sectional study of 9-year-old children (n = 1,194) was performed in 2007-2008. Using the international cutoff points and percentiles, we determined subjects with elevated blood pressure, hypertriglyceridemia (>= 90 percentile), low HDL-C (<= 10 percentile), and elevated fasting glucose (100mg/ dL). We compared several anthropometric indices [triceps skin-fold thickness (SFT), waist circumference, hip circumference, waist-to-hip ratio, body mass index (BMI) and waist-to-height ratio] and their association with metabolic syndrome risk criteria other than waist circumference among 9-year-old children. Results: Metabolic syndrome risk criteria were commonly observed among 9-year-old children: 244 students (20.4%) had hypertriglyceridemia and/ or low HDL-C, 362 students (30.3%) had elevated blood pressure, and 254 (21.3%) students were overweight or obese. Among covariates of SFT, BMI, waist circumference, waist-tohip, or waist-to-height ratio categories, the BMI category was the only significant predictor of having two or more metabolic syndrome risk variables [odds ratio (OR) = 3.5, 95% confidence interval (CI) 1.69-7.41, P = 0.001 for boys and OR= 4.7, 95% CI 1.61-13.55, P = 0.005 for girls]. Conclusions: Assessing anthropometric indices is crucial for early detection and prevention of metabolic syndrome among children and adolescents. Age-and sex-specific cutoff points of BMI can be used to screen for the metabolic syndrome and related risk criteria among 9-year-old children.
Keywords: CARDIOVASCULAR RISK-FACTORS; OVERWEIGHT; ADOLESCENTS; DEFINITION; OBESITY; HEIGHT; RATIO